Epiretinal membrane surgery outcome in eyes with abnormalities of the central bouquet - Brinkmann, Max P. (Int J Retina Vitreous, 2021)
BACKGROUND: Clinical studies have shown that epiretinal membranes (ERM) as well as abnormalities of the central foveal bouquet (CB) can be classified in different stages according to their morphological appearance. Furthermore, visual acuity correlates with the different stages of these features. The present study evaluated how these findings change after the surgical removal of the ERM and their impact on functional outcomes. METHODS: In this retrospective study eyes with ERM were evaluated by SD-OCT scans before and after pars plana vitrectomy (PPV) with macular ERM and internal limiting membrane (ILM) peeling. CB abnormalities were classified according to their morphological appearance from stage 0 (no abnormalities) to stage 3 (acquired vitelliform lesion). ERMs were classified ranging from stage 0 (absence of ERM) to stage 4 (ERM with significant anatomic disruption of macula). Changes in morphology were correlated with visual acuity before and after surgery. RESULTS: 151 eyes were included into the study. Before surgery 27.2% (n = 41) of eyes showed CB abnormalities with stage 1 being the most common (11.9%, n = 18). Before surgery ERM was seen in all patients. The most common form was stage 1 (28.5%, n = 43), followed by stage 3 (27.8%, n = 42) and 2 (25.2%, n = 38). Only 18.5% (n = 28) presented with stage 4 ERM. The mean BCVA was 0.42 (logMAR) before and increased to 0.19 (logMAR) 8 weeks after vitrectomy (95% CI 0.20–0.28; p < 0.001). Patients who suffered from CB abnormalities had less increase in BCVA than patients who had no evidence of CB (0.28 vs. 0.14 logMAR; p < 0.001). Of all the patients with CB abnormalities at baseline, 68% had lower CB grading after the surgery (n = 28; 95% CI; p < 0.001). All patients showed an improvement of their ERM grading, with 98.7% reaching stage 0 (n = 151 vs. n = 149; 95% CI; p < 0.001). CONCLUSIONS: The study indicates that the presence of CB abnormalities correlates with worse visual function. They are furthermore associated with worse visual outcomes after PPV with ERM and ILM peeling. These findings are valuable for deciding on PPV in patients with ERM.